ANALYSIS OF FARMERS' INSURANCE LITERACY IN ACEH BESAR DISTRICT, ACEH PROVINCE - Liston Siringo Ringo; Hermanto Siregar; Nunung Kusnadi; Harianto; Bagio (RADJA PUBLIKA, 2024)
Insurance literacy plays a crucial role in expanding farmers' access to insurance. Lack of understanding of insurance products and inability to process information prevent farmers from making the right decisions, which leads to low levels of insurance participation. This study aims to analyze the level of knowledge, attitudes, and behavior of farmers towards insurance and examine the factors that influence farmers' insurance literacy. Data were collected directly from 94 farmer households in four sub-districts in Aceh Besar Regency. This study measured farmers' insurance literacy using a questionnaire and then conducted a regression analysis using the ordinary least squares (OLS) method on variables suspected of influencing insurance literacy. The results of this study indicate that farmers' insurance literacy is sufficient literate. Variables such as gender, age, education level, and main occupation significantly affect farmers' understanding of insurance. The average scores of farmers' knowledge, attitudes, and practices towards insurance were 42.23, 71.36, and 46.28, respectively. Education has a significant impact on farmers' knowledge of insurance. This study suggests that the government and other stakeholders can carry out promotional activities, socialization and training periodically to increase insurance knowledge and awareness.